Toxicidad y repelencia de aceites esenciales en plagas de almacen del arroz - Pascual-Villañobos, M.J.=700 1 Ballesta-Acosta, M.C.; Soler, A.
(En, Es)
ilus., 10 ref.
Keywords: SITOPHILUS ORYZAE; RHYZOPERTA DOMINICA; CRYTOLESTES PUSILLUS; CARUMM CARVII; CORIANDRUM SATIVUM; OCIMUM BASILICUM; ACEITES ESENCIALES; ARROZ; CONTROL BIOLOGICO; ESPAÑA; METIL CHAVICOL; LINALOL